Water-induced hyperhydration increases total body water to a greater extent than glycerol-induced hyperhydration: a case study of a trained triathlete - Goulet, E.; Labrecque, S.; Melancon, M. O.; Royer, D. (Journal of Sports Science & Medicine, 2002)
Glycerol-induced hyperhydration (GIH) prior to endurance exercise is a strategy that is increasingly used by athletes. Compared with water-induced hyperhydration (WIH), GIH has been shown to reduce diuresis, thereby increasing total body water (TBW). It has never been demonstrated that WIH proved to be more efficient than GIH for increasing TBW. Therefore, we report the case of a trained triathlete in whom WIH, compared with GIH, increased TBW during a 110-min hydration protocol. On two separate days the subject ingested, in a randomized double blind fashion, either 26 ml.kg-1 body mass (BM) of water or 26 ml.kg-1 BM of water with 1.2 g glycerol.kg-1 BM. Compared with GIH, WIH increased TBW by an additional 511 ml. It is proposed that WIH was effective in decreasing urine output and, therefore, in augmenting TBW, because the water ingested during this treatment was integrated into the body fluid pools relatively more slowly than that ingested during GIH. Practically, this finding implies that it could thus be possible for researchers and athletes to find out that on occasion WIH increases TBW more than GIH over a period of hydration of 2 h.